Forensic value of orthodontic records for human identification: a systematic review - Pires, Cristian Duane; Silva, Douglas Teixeira da; Paranhos, Luiz Renato; Franco, Ademir (Acta Scientiarum. Health Sciences, 2024)
Extensive dental records are produced for orthodontic planning and treatment. Photographs, radiographs, and descriptive data used to register patient progress have benefited the fields of civil litigation and human identification. This study aimed to perform a systematic literature review guided by the following question: What type of orthodontic antemortem (AM) data have been used more often to confirm human dental identifications? The research protocol followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) and the Joanna Briggs Institute (JBI) manual. Registration was made in Open Science Framework. Ten databases were searched (LILACS, BBO, Cumed, Embase, MedLine [PubMed], SciELO, Scopus, Web of Science, Easy Dans, and BDTD). The eligible studies were only descriptive observational and should address the topic of human identification using orthodontic AM data. The risk of bias was assessed with the JBI tool. The initial search found 2,216 studies, of which 16 were eligible. Clinical photographs and panoramic radiographs were the most common orthodontic AM data. Most human identification cases relied on morphological (e.g., rotation and crown shape) and therapeutic (e.g., orthodontic appliances and restorations) identifiers. Orthodontic records can support human identification with relevant dental evidence, especially when providing images (radiographic or not). Forensic dentists should understand proper image analysis to interpret and detect morphological and therapeutic identifiers of forensic value.